The Effectiveness of Intergenerational Communication-Based Intervention to Reduce Psychological Distress in Young Adults Experiencing Conflict Related to Marriage Plans - Choiriyah, Lilik Mudloyati; Hanum, Lathifah (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Topics of wedding plans can trigger disagreements in communication between young adults children and parents. Communication problems with parents can reduce the quality of relationships and increase stress on individuals, particularly if the issue has escalated into conflict. The quality of the relationship between young adults and their parents is significant to note in maintaining mental health by reducing stress. This study aims to examine the effectiveness of intergenerational communication-based intervention in reducing stress in young adults who experience communication problems with their parents regarding marriage plans. We conducted group intervention for young adults aged 18 to 29 with communication problems with their parents regarding marriage. Changes in the way of communication were assessed with the Global Perceptions of Intergenerational Communication Scale (GPIC) score, stress level with the Perceived Stress Scale (PSS) score, and life satisfaction with the Satisfaction with Life Scale (SWLS) score given before and after the intervention. Results found that emotion regulation, perspective-taking, and assertive communication taught through group intervention effectively help improve intergenerational communication skills, reduce stress levels, and increase life satisfaction in young adults. Considering the contribution of conflict with parents to stress levels, interventions based on intergenerational communication are considered worthwhile in overcoming psychological distress.